Napoleon Reversing the French Revolution. - Kapoor, Heena (HPS: The Journal of History and Political Science, 2015)
Napoleon Bonaparte turned France into a police state during his reign.[1] However, he did not continue the French Revolution as the French people hoped. The French Revolution brought forth liberty and to do as ones will if it does not harm another.[2] A new document brought by the French Revolution embodying these principles was the French Declaration of Rights of Man and Citizen in 1789.[3] This Declaration stated under article 11 that there was to be a free flow of ideas and opinions in writing and the press.[4] Article 7 outlawed any cruel harsh punishment and arbitrary sentencing.[5] However, Napoleon reversed these fundamental principles of the French Revolution. Writers, the press, along with the French people were subjected to the General police and prefects and were banned from saying anything controversial, against his regime, anything about France’s revolutionary past, and against France’s allies.[6] Arbitrary, cruel punishments, and harsh rules were enacted by Napoleon through the Penal Code in 1810.[7] Napoleon did not continue the French Revolution and reversed it by turning France into a police state and monitored and censored the French people, the press, and writers.